Strategy to Increase Padang City Government Apparatus' Capacity in Dealing with Earthquake and Tsunami - Andree Harmadi Algamar (International Journal Labs, 2022)
Indonesia's West Sumatra is one area that has drawn attention due to a significant potential threat. With a 4,229,730 ha area, the province is rich in both historical significance and scenic beauty. On the other side, West Sumatra Province should be on guard against potential disasters. The goal of this study is to describe and analyze the capacity of the Padang City Government's capacity to prepare for earthquake and tsunami disasters, as well as the supporting and inhibiting factors for increasing that capacity. It also seeks to identify the best strategy and strategy model for increasing the Padang City Government's capacity to prepare for earthquake and tsunami disasters. The researcher came to the conclusion that the dimensions of goals, attributes, self-concept, knowledge, and skills are crucial to enhancing the ability of the Padang City Government in preparation for earthquake and tsunami catastrophes based on the findings and previous talks. The ANDREE (Ability, Nationality, Drill, Rescue, Empowering, Efficient) approach is therefore recommended in this situation, according to academics.